Microwave Power Detectors in Different CMOS Design Architectures : A Review - Jules Guiliary, Ravanne; Yi Lung, Then; Hieng Tiong, Su; Ismat, Hijazin (IEEE, 2022)
Transmitted and received power must be controlled quickly and accurately to comply with government regulations, minimize interference, and optimize power consumption. Microwave power detectors (PDs) are critical building blocks employed in applications such as integrated circuit tests and measurements, wireless communication, and automatic-gain-control (AGC) circuits to monitor signal power level. PDs are utilized as received signal strength indicators (RSSIs) to adjust the gain of the intermediate frequency/RF signal via an AGC circuit [1]. They are also used in mobile terminals to monitor the transmitted power, thereby optimizing power consumption. Two popular methods employed to measure the power signal level are root mean square (RMS) value and peak value. Peak detectors capture the input’s peak power to provide power information, whereas the RMS PD provides information about the average power [2]. Figure 1 shows a conventional block diagram of a microwave PD employed in an RF transmitter. The directional coupler is used to couple the output signal from the power amplifier to a PD. The signal is then converted to a dc voltage that the power controller utilizes to change the power amplifier’s gain, thereby improving the transmitter’s linearity.